Campus Aerials - Surveying, 1968 (1968)
Series of 27 surveying photographs: 1 (ua-pho_00001206): Highway 1, Residences across from Cal Poly, where Highland runs through, Pacheco Elementary School; 2 (ua-pho_00001205): Highway 1, Residences across from Cal Poly, where Highland runs through, Pacheco Elementary School; 3 (ua-pho_00001208); 4 (ua-pho_00001187): Yosemite Towers visible, baseball diamond; 5 (ua-pho_00001200): Main campus, Science Building, Engineering East, Engineering West, North Mountain, Administration building, Erhart Agriculture, Agricultural Engineering, some residences off campus; 6 (ua-pho_00001212): Main campus, Science Building, Engineering East, Engineering West, North Mountain, Red Brick dormitories, Yosemite towers, Administration building, Erhart Agriculture, Agricultural Engineering, some residences off campus; 7 (ua-pho_00001192): Main campus, Science Building, Engineering East, Engineering West, North Mountain, Administration building, Erhart Agriculture, Agricultural Engineering, some residences off campus; 8 (ua-pho_00001204): California Boulevard; 9 (ua-pho_00001207): Radio Tower Hill, Highway 1; 10 (ua-pho_00001194): Radio Tower Hill, Highway 1; 11 (ua-pho_00001201): Radio Tower Hill, Highway 1; 12 (ua-pho_00001198): Residences west of campus near Radio Tower Hill, site of present-day Nativity of Our Lady church; 13 (ua-pho_00001203): Poly Canyon; 14 (ua-pho_00001189): Agricultural Engineering, Aero Hangar, Machine Shop, Herdsman House - right side of image is cut off, missing frame; 15 (ua-pho_00001190): Campus sports fields near Aero Hangar and Machine Shop; 16 (ua-pho_00001191): Mt Bishop Road; 17 (ua-pho_00001188): Highway 1, Mt Bishop Road, Stenner Creek Road; 18 (ua-pho_00001193): Highway 1, Mt Bishop Road, Stenner Creek Road; 19 (ua-pho_00001210): Highway 1; 20 (ua-pho_00001195): Poly Canyon, North Mountain dorms, Alan A. Erhart Agriculture Building; 21 (ua-pho_00001211): Poly Canyon, some of main campus; 22 (ua-pho_00001197): Some of main campus, where present-day parking lots are, Agricultural Engineering; 23 (ua-pho_00001202); 24 (ua-pho_00001196): Highway 1, Mt Bishop Road; 25 (ua-pho_00001185): Highway 1, Stenner Creek Road, Mt Bishop Road; 26 (ua-pho_00001209): Highway 1, Stenner Creek Road, Mt Bishop Road; 27 (ua-pho_00001186): Highway 1, Stenner Creek Road